Test of memory-enhancing raisin product in swiss mice by using Radial Arm Maze / Nur Farhah Hafizah Ab Hamid - Ab Hamid, Nur Farhah Hafizah (2013)
Memory is one of the most vital components in life and it is the process which information is encoded, stored and retrieved. Memory has become very important in daily life especially in learning. The fact that memory is very important have lead to the creation of product which might boost the memory. A lot of memory-enhancing product that which available in the market. In this study, one of the memory enhancing products, product Y (which contain raisin as major ingredient) was used to know the effect especially in spatial memory improvement of mice. The performance of the mice was assessed using Radial Arm Maze (RAM). The dose for the product was determined based on body weight of the mice and two doses of product Y (200 mg/kg and 400 mg/kg) were used. The controls used were normal saline (negative control) and piracetam (positive control). The doses were given by force feeding into four different groups (five mice in each group) for 14 days. On the last three days of the two weeks treatment, the real RAM experiment was started. The result showed that piracetam had significant effect on the performance of the mice this study. This study does not really support the hypothesis that the product has positive effects in enhancing memory. The other experimental model might be used in order to achieve a better result.